Comparative physiological and soil microbial community structural analysis revealed that selenium alleviates cadmium stress in Perilla frutescens - Yang, Xiaohuan; Li, Ying; Ma, Jinhu; Wu, Fei; Wang, Liyin; Sun, Liangliang; Zhang, Ping; Wang, Wenying; Xu, Jin (Frontiers in Plant Science, 2022)
Cadmium (Cd) toxicity not only affects plant growth and development, but also affects human health through the food chain. Several studies have demonstrated that Selenium (Se) alleviates Cd stress in plants; however, whether and how Se-alleviated Cd stress by regulating the structure of soil microbial community remain largely unclear. Here, we investigated the alleviating effects of exogenous applied Se (foliar spraying or root application) on plant growth under Cd stress in perilla (Perilla frutescens L.) by measuring the biomass, photosynthetic fluorescence parameters, root cell wall components and soil microbial community structure and diversity. Under Cd stress, perilla seedlings supplemented with Se increased chlorophyll content. Foliar spraying Se increased the levels of relative chlorophyll content (ΦII), photosynthetic system II (ΦPSII) and electron transport rate (ETR) in perilla leaves under Cd stress; while, root application of Se increased the levels of photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), water use efficiency (WUE) and stomatal limitation value (Ls) under Cd stress. Compared with Cd toxicity alone, root application of Se increased the contents of hemicellulosic 1 and hemicellulosic 2 in the cell wall of perilla roots. Cd toxicity or root application of Se did not affect soil bacterial community diversity. Root application of Se increased the relative abundance of Proteobacteria, Bacteroidetes, Fibrobacteres, Sphingomonas and Nitrosospira in Cd-contaminated soil, and thereby improving soil microbial community structure, finally promoting the growth of perilla seedlings.